A prophylactic protocol to stimulate the immune response also controls infectious disease and, consequently, minimizes diarrhea in newborn heifers. (August 2018) - Volpato, Andreia; Da Silva, Aleksandro S.; Crecencio, Regiane B.; Tomasi, Thainã; Fortuoso, Bruno F.; Ribeiro, Marluciana P.; Secco, Rodrigo; Pereira, Wanderson A.B.; Bottari, Nathieli B.; Schetinger, Maria Rosa C.; Morsch, Vera Maria M.; Baldissera, Matheus D.; et al.
Abstract: The immunostimulatory and immunomodulatory properties of selenium (Se), an essential trace element for animals, has increase its use because may prevent/or reduce the occurrence of infectious diseases. Thus, the aim of this study was to verify whether Se and vitamins (A and E) applied via subcutaneous associated with secnidazole via oral exert positive effects in the antioxidant and immune systems, as well as whether prevent infections caused by protozoan and bacteria, and consequently, reduce the number of cases of diarrhea in heifers. Thirty-two newborn Holstein heifers were divided into two groups with sixteen animals each: the control group and the treated group that received sodium selenite (0.2 mg/kg) and vitamins A (35 mg/kg) and E (1 mg/kg) with one day of life, and a second application associated with secnidazole (400 mg/animal) on day 10 of life. Sample collection (blood and feces) were performed on days 1, 15, 30, 45 and 60 of life. Heifers from the treated group showed higher hematocrit values compared to the control group on day 60 of life, while total serum protein levels were higher on days 15 and 30. The ceruloplasmin (days 15, 30 and 60), IgG of heavy chain (days 15, 30, 45 and 60), IgG of light chain (days 45 and 60) and haptoglobin (days 15, 30, 45 and 60) were higher in the treated group compared to the control group. Serum levels of glucose decreased in treated animals on day 60 of life, while serum levels of albumin, triglycerides, urea, cholesterol, thiobarbituric acid reactive substances, reactive oxygen species and glutathione S-transferase activity did not differ between groups. Secnidazole was able to prevent infections caused by Giardia duodenalis in the first few days of life, but no difference was observed between groups. Moreover, there was no difference on total bacteria count and the incidence of diarrhea between groups. No difference on weight gain was observed on day 60 of life, but on day 210 of life treated animals had higher weight gain compared to the control group. Based on these evidences, we concluded that the injectable application of Se and vitamins (A and E) associated to secnidazole can improve the immunological system, and consequently, favor animal's performance. Highlights: Proper management of heifers is a crucial activity in milk farms. Young animals are susceptible to various diseases, and therefore, prophylactic protocols are important. Metaphylactic effect of sodium selenite and vitamins (A and E) associated to the oral treatment with secnidazole in calves. Have positive effect on the antioxidant and immune systems in animals. Prevents infections caused by protozoan and bacteria, and reduces the incidence of diarrhea in heifers.